2005
DOI: 10.4049/jimmunol.175.12.8354
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Allergenic Potency of VR9-1, a Mutant of the Major Shrimp Allergen Pen a 1 (Tropomyosin)

Abstract: The major shrimp allergen, tropomyosin, is an excellent model allergen for studying the influence of mutations within the primary structure on the allergenic potency of an allergen; Pen a 1 allows systematic evaluation and comparison of Ab-binding epitopes, because amino acid sequences of both allergenic and nonallergenic tropomyosins are known. Individually recognized IgE Ab-binding epitopes, amino acid positions, and substitutions critical for IgE Ab binding were identified by combinatorial substitution anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 48 publications
4
101
0
4
Order By: Relevance
“…␣S1-casein is considered as a true food allergen, also classified as class I food allergen, which is comparable to the major fish allergen parvalbumin (31), the major peanut allergens (Ara h 1, Ara h 2, Ara h 3) (32), and the major shrimp allergen (33), and it can induce severe and life-threatening anaphylactic reactions. Interestingly, we found that Ͼ50% of patients with gastrointestinal symptoms, skin and respiratory symptoms, or severe systemic reactions, but fewer patients with only skin symptoms, showed IgE reactivity to r␣S1-casein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…␣S1-casein is considered as a true food allergen, also classified as class I food allergen, which is comparable to the major fish allergen parvalbumin (31), the major peanut allergens (Ara h 1, Ara h 2, Ara h 3) (32), and the major shrimp allergen (33), and it can induce severe and life-threatening anaphylactic reactions. Interestingly, we found that Ͼ50% of patients with gastrointestinal symptoms, skin and respiratory symptoms, or severe systemic reactions, but fewer patients with only skin symptoms, showed IgE reactivity to r␣S1-casein (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Of these four proteins, α S1 -casein thought to be the most potent for inducing a specific IgE response [1]. α S1 -casein is considered as a true food allergen, also classified as class I food allergen, which is comparable to the major fish allergen parvalbumin [21], the major peanut allergens [13], and the major shrimp allergen [15], and it can induce severe and life-threatening anaphylactic reactions. α S1 -casein, which is a single-chain linear phosphoprotein of 199 amino acid residues, has only a small amount of secondary structure and lacks disulfide bonds, which results in a reduction of tertiary interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…Reese et al [4] constructed a hypo-allergen VR9-1 by converting 12 critical amino acids located in the five IgE epitope regions in the shrimp tropomyosin Pen a 1 previously mapped [14] into homologous sequences of the non-allergenic vertebrate tropomyosin. Results showed that VR9-1 exhibited reduced allergenic potency up to 90-98% in a humanized rat basophil leukemia cells (RBL) assay.…”
Section: Applications Of B Cell Epitopes In Therapymentioning
confidence: 99%
“…T cell epitopes refer to the short peptide fragments activating Th2 via MHC class II molecules while B cell epitopes, or IgE-binding epitopes, refer to the regions recognized by IgE on the allergen. With the identification of B cell epitopes at the molecular level, hypo-allergens possessing reduced allergenicity can be constructed through the introduction of point mutations on these IgE-binding regions [3,4]. The lack of IgE reactivity reduces the risk of these hypo-allergens to form cross-links with IgE and thus prevents the development of allergic side effects during treatment [5].…”
Section: Introductionmentioning
confidence: 99%